The effect of mindfulness-based Tai Chi Chuan on mobile phone addiction among male college students is associated with executive functions - Jizhao Li; Dongling Wang; Shuang Bai; Wanjiao Yang (PLoS ONE, 2025)
Objective Mindfulness-based Tai Chi Chuan (MTCC) have been shown to contribute to improvements in cognitive and executive functions. Changes in inhibition, an aspect of executive function, have been closely linked to mobile phone addiction. However, the relationship between these elements remains unclear. This study aims to investigate the effects of an 8-week MTCC intervention on executive function, mindfulness levels, and mobile phone addiction in male college students. Additionally, the study explores the role of executive function in improving mobile phone addiction through MTCC interventions. Methods Sixty-six male college students were selected as research subjects and randomly divided into a control group (33) and an experimental group (33). The control group maintained their normal physical activity levels without any additional intervention. In contrast, the experimental group underwent 8 weeks of MTCC training. Mindfulness levels were assessed using the Mindful Attention Awareness Scale (MAAS), while mobile phone addiction was evaluated by the Mobile Phone Addiction Index (MPAI). The Flanker task, 1-back task, and More-Odd Shifting task were employed to evaluate inhibition, updating, and shifting aspects of executive function, respectively. Results (1) The 8-week MTCC intervention significantly improved mobile phone addiction among male college students, with the intervention group showing a lower post-intervention MPAI score (46.09 ± 18.11) compared to the control group (56.55 ± 16.02), yielding a mean difference of −10.46 (95% CI: −18.92 to −1.99, p = 0.016). Mindfulness levels also improved significantly (p = 0.046), as did specific sub-functions of executive function: inhibition correct rate (p < 0.001), inhibition response (p = 0.001), and shifting correct rate (p = 0.001). No significant effects were observed for updating correct rate (p = 0.527) or updating response (p = 0.303). (2) Mobile phone addiction indices were significantly correlated with changes in inhibition response (r = 0.756, p = 0.000 < 0.01), updating response (r = 0.035, p = 0.045 < 0.05), and shifting response (r = 0.397, p = 0.022 < 0.05). (3) Mindfulness levels and inhibition levels were significantly correlated (r = 0.394, p = 0.023 < 0.05). (4) Changes in inhibition within executive functions partially mediated the improvement of mobile phone addiction, with the direct effect (0.716) and mediating effect (0.483) accounting for 59.72% and 40.28% of the total effect (1.199), respectively. Conclusion MTCC exercises significantly increase cognitive functions, leading to increased inhibition and attentiveness, and may be helpful in the prevention of addictions, including cell phone addictions.